Efficacy of SCH39304 in murine cryptococcosis. - Restrepo, B I (1989)
Cryptococcal meningitis is increasing in frequency, in large part because of the advent of acquired immune deficiency syndrome. Using the murine cryptococcosis model, a new oral triazole, SCH39304, has been compared with two drugs in clinical use, fluconazole and amphotericin B. BALB/c mice (nu/nu and nu/+) were challenged intracerebrally or intranasally. Oral treatment was given daily with SCH39304 at doses of 1 to 60 mg/kg of body weight or fluconazole at doses of 1 or 5 mg/kg of body weight. Amphotericin B was given intraperitoneally three times weekly, at doses of 3 or 6 mg/kg. After intracerebral challenge, SCH39304 prolonged survival in doses as low as 1 mg/kg, a dose at which fluconazole was ineffective. At equal doses, SCH39304 consistently increased survival more than did fluconazole but not longer than did amphotericin B. SCH39304 significantly lowered colony counts in brains more than did fluconazole but no more than did amphotericin B. SCH39304 was also superior to fluconazole after intranasal challenge at equal doses. SCH39304 appears to be superior to fluconazole in mice when the drugs are given at equal doses. Clinical trials are warranted.